Loading 3-deazaneplanocin A into pegylated unilamellar liposomes by forming transient phenylboronic acid-drug complex and its pharmacokinetic features in Sprague-Dawley rats - Sun, F. (2014)
10.1016/j.ejpb.2011.10.014